Penerapan Kompor Briket Berbasis Sensor Suhu Untuk Meningkatkan Pemahaman Teknologi Hijau Pada Sentra Industri Batik Tulis Pemalang - Luthfianto, Saufik; Siswiyanti, Siswiyanti; Hidayat, Tofik; Nurwildani, M. Fajar; Zulfah, Zulfah; Sugiono, M. Cipto; Amanah, Inayatu (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2022)
The implementation of community service is located in the Center of Batik Tulis Pemalang Industry with the number of artisans as many as 20 people with the aim to find out the success of research programs applied to the community of batik industry centers in the Pemalang area. The method used is the method of experimenting the product application program and testing batik cloth by producing night penetrating power in batik cloth by 65% or an increase of 25% and night elasticity down 20% the average of the first application is 1.65, while the second application is 2.75, the correlation between the first and second applications is significant and the application of temperature sensor-based briquette stoves after socialization increases their understanding